Comparative Study of Print Media Coverage of Indian Athletes in London Olympics - Paul, Asish; Roy, Gopa Saha (Journal of Sports Research, 2015)
Sports became the most interesting area of media coverage among different stream. As it has got its most important status in the world’s media to popularize the newspaper, there is a distinct lack of comparative research on the media coverage of sports. To minimize the gap, this search draws attention on sports coverage during the London Olympics, 2012 from three different newspapers of different languages. The coverages were recorded considering the preview, competition and review phases. The results show that the total coverage of the English newspaper, the Telegraph (36039 sq. cm.) was more than the other two Bengali and Hindi newspapers (9224 sq. cm. and 2599 sq. cm. respectively). The female performers got more attention (34942 sq. cm.) than the male performers (12920 sq. cm.). All the three newspapers provided maximum coverage in the competition phase rather than the other two phases. The English newspaper provided more attention in preview of the main competition also in comparison to the other two newspapers. It has concluded that the coverage of the print media depends mainly on the performance of the athletes, popularity of the performers and intensity of the competition.